PERANCANGAN SISTEM PENDUKUNG KEPUTUSAN UNTUK MEMUDAHKAN PEMILIHAN KEDAI KOPI - Calvin,; Hugeng,; Sutrisno, Tri (Jurnal Ilmu Komputer dan Sistem Informasi, 2023)
A decision support system (DSS) for selecting coffee shops is a technological solution that can help coffee enthusiasts find coffee shops that suit their preferences. The purpose of this research is to design a decision support system to facilitate the selection of coffee shops. The methodology used in this research is the waterfall method which consists of needs analysis, design, implementation, and system testing. Needs analysis is carried out by conducting surveys and interviews with respondents who are coffee consumers. The results of the needs analysis will be used as the basis for system design. The system design is carried out using the ERD and DFD models, as well as the selection of the right programming language and database. Implementation is done by developing the system according to the design that has been made. Finally, system testing is carried out to ensure that the system can run properly and according to user requirements. It is hoped that the results of this study can provide benefits for coffee fans in choosing coffee shops that suit their preferences.